2021
DOI: 10.1183/23120541.00928-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multicomponent grading system for obstructive sleep apnoea: the Baveno classification

Abstract: New findings on pathophysiology, epidemiology, and outcome have raised concerns on the relevance of the apnoea-hypopnoea index (AHI) in the classification of obstructive sleep apnoea (OSA) severity. Recently, a multicomponent grading system, decision integrating symptomatology and comorbidities (Baveno classification), was proposed to characterise OSA and to guide therapeutic decisions. We evaluated if this system reflects the OSA population, if it translates into differences in outcomes, and if the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 40 publications
4
30
0
2
Order By: Relevance
“…However, contrary to the results of Joyeux-Faure et al [ 48 ], in our analysis aoPWV was strongly correlated with mean nocturnal O 2 Sa, which was also associated with weight, BMI, and WC. Our results are in line with the ”hypoxemic burden” theory in OSA patients, in which an integrated symptom–comorbidity approach aims to replace AHI as the central parameter in the OSA treatment algorithm [ 41 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, contrary to the results of Joyeux-Faure et al [ 48 ], in our analysis aoPWV was strongly correlated with mean nocturnal O 2 Sa, which was also associated with weight, BMI, and WC. Our results are in line with the ”hypoxemic burden” theory in OSA patients, in which an integrated symptom–comorbidity approach aims to replace AHI as the central parameter in the OSA treatment algorithm [ 41 ].…”
Section: Discussionsupporting
confidence: 84%
“…CPAP adherence in our study (51.28%) was significantly lower than that in previous reports [ 18 , 39 ], but similar to that observed by Dorkova et al [ 40 ] in patients with severe OSA and MS. The poor CPAP adherence could be explained by the relatively low average ESS score observed in our study group [ 41 ], as well as by the presence of MS per se [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a study using the “Baveno” classification, a multicomponent grading system for OSA [ 60 ], was tested in the ESADA cohort in 14 499 patients with a diagnosis of OSAS who were on treatment [ 61 ]. Groups were classified into patients with minor symptoms and cardiometabolic comorbidities (Group A), severe symptoms and minor cardiometabolic comorbidities (Group B), minor symptoms and severe cardiometabolic comorbidities (Group C) and severe symptoms and cardiometabolic comorbidities (Group D).…”
Section: Pathophysiology Endotypes and Phenotypes Of Osas: Importance To The Definitionmentioning
confidence: 99%
“…Approximately 70% of the patients in the entire group were on CPAP and a subgroup were followed up for 24–36 months. The major findings (apart from reasonable ease of classification) showed that Groups B, C and D improved on treatment with CPAP on several cardiometabolic parameters and that the AHI did not improve the classification integrity [ 61 ].…”
Section: Pathophysiology Endotypes and Phenotypes Of Osas: Importance To The Definitionmentioning
confidence: 99%